Effect of Arc Plasma Sintering on the Structural and Microstructural Properties of Fe-Cr-Ni Austenitic Stainless Steels - Parikin, Parikin; Dani, M.; Dimyati, A.; Purnamasari, N. D.; Sugeng, B.; Panitra, M.; Insani, A.; Priyanto, T. H.; Mustofa, S.; Syahbuddin, Syahbuddin; Huang, A. (UI Scholars Hub, 2021)
X-ray diffraction techniques were performed to determine the actual crystal structure of A2 austenitic stainless steel (ASS) as-cast and A2 ASS after arc plasma sintering (APS) for 2 s. Computations were conducted on the basis of the Bragg arithmetic formula by comparing the S2 arithmetic with the interplanar spacing. The Bragg arithmetic formula is a simple series for the determination of the crystalline phase of materials based on the Miller indices of cubic shapes or other shapes. A2 ASS as-cast was identified to have a crystal structure of face-centered cubic with lattice parameter a = 3.58 Å. A similar crystal structure can still be detected in A2 ASS after APS for 2 s with lattice parameter a = 3.60 Å. This finding was confirmed by neutron diffraction measurements and optical–electron microscopy observations. Under the same conditions, both A2 ASS as-cast and A2 ASS after APS for 2 s have similar cast structures. The grain boundary formed in A2 ASS as-cast is thinner than that in A2 ASS after APS for 2 s, which is visible in its boundaries. Moreover, the grain structure of A2 ASS after APS for 2 s, which was originally elongated particles, became globular particles. Similarly, granular precipitates became concentrated and encompassed the steel matrix along the grain boundaries. Furthermore, scanning electron microscopy with energy-dispersive X-ray analysis showed that particles and islands in steel are distributed in the grains and at the grain boundaries, respectively. Precipitates are composed of C, Cr, Fe, and Ni. The elemental contents of Cr and C are dominant; thus, Cr23C6 precipitate is formed at the grain boundaries.